Surfactant free synthesis of Au@Ni core-shell nanochains in aqueous medium as efficient transfer hydrogenation catalyst - Vysakh, A. B.; Shebin, K. J.; Jain, Ruchi; Sumanta, P.; Gopinath, Chinnakonda S.; Vinod, C. P. (Applied Catalysis A-General, 2019)
A surfactant free aqueous phase synthesis method is reported for the generation of highly lattice mismatched Au@Ni core-shell nanochains without using any expensive and hazardous organic ligands. As synthesised Au@Ni nanochain structures showed high thermal stability and bulk oxidation resistance up to 300 degrees C. In situ near ambient pressure XPS (NAPXPS) analysis has been done for the bare Au@Ni nanochain surfaces under oxygen atmosphere and at different temperatures which showed evidence for the surface oxidation resistance of naked Au@Ni nanochains up to 200 degrees C. Ligand or capping agent free Au@Ni nanochain surfaces are found to be highly active for transfer hydrogenation of acetophenone to 1-phenyl ethanol an important commodity in perfumery industry.
Keywords: Au@Ni nanochains; core-shell; NAPXPS; Surfactant free; synergistic effects; transfer hydrogenation